Influence of the time of the day and chronotype on speed abilities in junior team ice hockey players - Palov, R. (SportLogia, 2014)
The aim of the study was to compare the effect of time of day and chronotype on the speed abilities on the sample of junior ice hockey players (n = 20; defenders = 8, forwards = 12; age = 17.05 ± 1.34 years) playing in a competitive year 2013/2014 of Slovak extraligue of juniors. The influence of time of day and chronotype was detected on indicators of speed abilities (speed acceleration of lower legs). The test of acceleration speed was test time measured during the day on the basis of circadian rhythms of players, at 9 o`clock in the morning and 17 o`clock in the afternoon after the warm-up of the players (spaces of ice stadium Banská Bystrica). The criterion of performance evaluation was the average test time. We used Wilcoxon Signed Ranks Test (a = .01) to determine the significance of differences between morning and afternoon performance. Study has result in a different level of morning and afternoon levels of speed abilities that has shown that afternoon performance was higher than the morning. At up to 17 players we observed a higher level of speed abilities in the afternoon, thereof in 7 players the difference was in the level of statistical significance. Only in 3 of players we observed a higher level of speed abilities in the morning. Post hoc analysis have showed better average afternoon time (8.58 ± .17 s) than average morning time (8.65 ± .19 s). We found statistically significant differences p < .01. Based on analysis of chronotype in the file, we found that 15 (75%) players of research group consisted mostly balanced types, 3 (15%) players were evening type and 2 (10%) players morning type. The time of players has not showed a main effect of test time-of-day or chronotype (F = .56, p = .46; F = .08, p = .92). The interactions between the factors were not statistically significant (test time of the day x chronotype: F = .03, p = .97). Evaluating the level of speed abilities of players in terms of chronotype and time of the day, we concluded that chronotype and time of the day has not main influence at the achieved level of speed abilities.i learning.